(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Artificial intelligence (AI) is rapidly changing the dynamics of global governance—not just through technological advancement, but by subtly unsettling the legal principles that have long underpinned public international law (PIL). Traditionally built around human judgment, sovereign authority, and clear lines of accountability, PIL now faces a shifting landscape where machine-driven processes play an increasingly central role. This piece explores how AI is beginning to shape the development of new international legal norms. It does so by looking at how international organizations are deploying AI, what legal and ethical dilemmas arise from its use, and how current regulatory frameworks are either adapting or falling short. While soft law instruments and a few treaty-based efforts have shown early signs of progress, notable gaps persist—especially when it comes to assigning responsibility, ensuring transparency, and upholding data sovereignty.